2014
DOI: 10.1016/j.rbmo.2013.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Telomere length in human blastocysts

Abstract: This is a retrospective study aiming to assess telomere length in human embryos 4 days post fertilization and to determine whether it is correlated to chromosomal ploidy, embryo developmental rate and patient age. Embryos were donated from patients undergoing treatment in the assisted conception unit. Seven couples took part, generating 35 embryos consisting of 1130 cells. Quantitative fluorescent in-situ hybridization (FISH) measured the telomere length of every cell using a pan-telomeric probe. Conventional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 57 publications
3
12
0
Order By: Relevance
“…Our data shows significantly shorter RTL in spontaneously eliminated embryos with aneuploid (with trisomy of chromosome 21 or 16, triploidy and monosomy X) karyotype, regardless of the type of aneuploidy. Similar results were shown [ 30 , 31 ] for aneuploid oocytes and embryos at the cleavage stage, although the telomere length was aligned at the blastocyst stage. The results of studies of telomere length in newborns with trisomy 21 (Down syndrome) are conflicting - from the claim of shortening [ 47 ] or lack of a likely difference in telomere length [ 48 ] to a probable elongation of telomeres in newborns with trisomy 21 versus newborns without chromosomal anomalies [ 49 ].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Our data shows significantly shorter RTL in spontaneously eliminated embryos with aneuploid (with trisomy of chromosome 21 or 16, triploidy and monosomy X) karyotype, regardless of the type of aneuploidy. Similar results were shown [ 30 , 31 ] for aneuploid oocytes and embryos at the cleavage stage, although the telomere length was aligned at the blastocyst stage. The results of studies of telomere length in newborns with trisomy 21 (Down syndrome) are conflicting - from the claim of shortening [ 47 ] or lack of a likely difference in telomere length [ 48 ] to a probable elongation of telomeres in newborns with trisomy 21 versus newborns without chromosomal anomalies [ 49 ].…”
Section: Discussionsupporting
confidence: 87%
“…Few recent studies mainly focused on preimplantation stages of human embryonic development available due to preimplantation diagnostic procedures [ 30 33 ]. According to the recent data, aneuploid human polar bodies possess significantly shorter telomeres than euploid polar bodies from sibling oocytes, although, at the blastocyst stage, telomeres did not differ in euploid and aneuploid embryos [ 30 , 31 ]. It is also likely that the chance of successful in vitro fertilization decreases along with the decrease in TL in oocytes.…”
Section: Introductionmentioning
confidence: 99%
“…In mosaic cleavage-stage embryos, aneuploid cells were reported to have shorter telomeres compared with chromosomally normal cells from the same embryo. Additionally, shorter telomeres were observed in the embryos of patients of advanced reproductive age who had a history of repeated spontaneous abortion, hinting at a potential role for telomeres in viability at later stages of development (after establishment of a pregnancy) (Mania et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, the telomeres in the oocytes begin shortening during fetal oogenesis, and this process is continued in the adult ovary, probably due to the chronic effects of oxidative and genotoxic stress, the late exit of the female gametes from their cell cycle arrest, as well as to a reduced activity of the telomerase ( 68 , 70 , 71 ). Furthermore, it has been demonstrated that the telomeres are shorter in oocytes from women who experienced IVF failure or recurrent miscarriage ( 72 ), as well as in oocytes resulting in fragmented ( 73 ) or aneuploid embryos ( 74 ). To this regard, Keefe and colleagues postulated the evolutionistic “telomere-mediated oocyte aging” theory: preventing AMA women from conceiving would, in turn, prevent them from dying because of childbirth, thereby affecting the reproductive fitness of their offspring ( 70 , 75 ).…”
Section: Putative Mechanisms Impaired By Aging and Leading To A Reducmentioning
confidence: 99%